Social Criticism as Digital Political Discourse: A Semiotic Analysis of Bintang Emon’s YouTube Stand-Up Comedy - Fajarina; Akhmad Abdul Muhyi (Universitas Multimedia Nusantara, 2025)
Stand up comedy has now developed from just a means of entertainment into a kind of public space to freely voice aspirations and social criticism. On several occasions, comedians also often reveal material about inequality, injustice, and hypocrisy that occurs in society by highlighting developing issues, in addition, social criticism through stand up comedy has a fairly important role in revealing social realities that are often overlooked. This study aims to determine how Bintang Emon uses semiotic elements to convey social criticism in his stand-up comedy on YouTube. The research method used is the Charles Sanders Peirce semiotic analysis method which focuses on three main elements, namely signs, objects, and interpretations with a qualitative approach. The results of the study showed several findings, including the first that resistance to social criticism in stand-up comedy occurs because of the use of verbal signs such as word choice, analogies and punchlines, as well as non-verbal signs such as gestures and intonation can be interpreted as a form of sarcasm, and the second, stand-up comedy through the YouTube platform becomes a kind of virtual community to spark dialogue in building public awareness and encouraging critical discussion of social and political issues.